On Things Past - Sharifah Sophia, Wan Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2012)
This essay considers two approaches at looking into our past. It inclines to support the view that what we know about our past comes not from vague notions of ‘tradition’ or ‘faithful memory’ or even ‘history’ but rather a matter of power position. The use of history by the dominant and the disenfranchised, represented here as the state and the revisionist narrative shows that history is a contemporary production and manifestation of power and contest.